Analisa Penerapan Statistical Quality Control Dalam Mengurangi Produk Cacat Pada Kerupuk Udang - Devina Ayu Ristanti; Ida Ayu Nuh Kartini (Jurnal Publikasi Ilmu Manajemen, 2023)
A company is always looking for the minimum raw materials (price) and looking for the maximum gain (profit). Companies cannot stand alone, companies coexist through other components, one of which is a good level of production. Often there is a misalignment between the product made and the desired product. The purpose of writing this thesis is to see the level of a product, to apply a level control system, and to see the factors that cause defective products. This research was applied at the company PT Titani Alam Semesta, for 30 days from February 06 - March 06, 2023. This research utilizes the quota sampling method by randomly sampling a total of 1000 kilograms of export-type shrimp crackers within 1 hour and will later be processed by utilizing the P control map. The check sheet results show the number of defective cracker products totaling 300 kilograms of shrimp crackers, Central Line Analysis (CL) of 0.01, the calculation gain (UCL) of 0.019, and the calculation gain (LCL) of 0.001. Based on the research applied regarding the analysis of the application of Statistical Quality Control in minimizing the total defective products at the company PT. Titani Alam Semesta Gresik, a conclusion can be drawn that there is still a need for a good level of improvement so that the level of production can increase and can produce good products.